Post-Traumatic Stress Disorder and the Earnings of Military Reservists - Loughran, David S. (RAND Corporation, 2013)
An investigation of the effects of having symptoms of post-traumatic stress disorder (PTSD) on the labor market earnings of reservists in the years following deployment.